(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2011)
The outcome of anaesthesia in coronary artery surgery depends partly on the duration of invasive manipulations including endotracheal intubation. It is ideal to avoid prolonged mechanical ventilation and attempt early extubation. Depressant effect of some anaesthetic agents and narcotics makes it a common practice to ventilate the patients of coronary artery bypass graft (CABG) surgery overnight resulting in unsatisfactory respiratory and haemodynamic performance. This study was aimed at overcoming the effects of prolonged mechanical ventilation after CABG surgery by using Total Intravenous Anaesthesia (TIVA) and by extubating the patient early to achieve a better postoperative respiratory cardiovascular performance. The study was conducted prospectively on 40 patients between 40 to 60 years, divided into two groups of 20 patients each. Gr.-A received infusions of Propofol 2-6 mg/kg/hr, Fentanyl 0.5-1.25 mg/kg/hr and Pancuronium bromide 0.01mg/kg. Postoperatively Propofol was continued in infusion for one hour while Inj. Diclofenac sodium was used as an analgesic. Patients in group B received a typical conventional anaesthesia and were ventilated electively till next morning. The study showed that in CABG surgery, TIVA produces non-significant depression of post-operative respiratory performance which helps in early extubation compared to those receiving conventional anaesthesia and electively ventilated overnight. Key words: TIVA; CABG; Early extubation DOI: 10.3329/jbsp.v29i1.7164 J Bangladesh Coll Phys Surg 2011; 29:3-9